2005
DOI: 10.1002/chin.200504263
|View full text |Cite
|
Sign up to set email alerts
|

Contiguous Stereogenic Quaternary Carbons: A Daunting Challenge in Natural Products Synthesis

Abstract: One element of structure that invariably increases the difficulty of a chemical synthesis is the presence in the target molecule of contiguous all-carbon quaternary stereocenters. This Perspective will examine the most useful transformations and strategies devised recently for directly assembling this structural unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…Combining these categories, research on natural products accounts for approximately 48% of the NCEs reported from 1981-2002. Natural products provide a starting point for new synthetic compounds, with diverse structures and often with multiple stereocenters that can be challenging synthetically (Clardy and Walsh, 2004;Nicolaou and Snyder, 2004;Peterson and Overman, 2004;Koehn and Carter, 2005). Many structural features common to natural products (e.g., chiral centers, aromatic rings, complex ring systems, degree of molecule saturation, and number and ratio of heteroatoms) have been shown to be highly relevant to drug discovery efforts (Lee and Schneider, 2001;Feher and Schmidt, 2003;Clardy and Walsh, 2004;Piggott and Karuso, 2004;Koehn and Carter, 2005).…”
Section: Importance Of Medicinal Plants In Drug Discoverymentioning
confidence: 99%
“…Combining these categories, research on natural products accounts for approximately 48% of the NCEs reported from 1981-2002. Natural products provide a starting point for new synthetic compounds, with diverse structures and often with multiple stereocenters that can be challenging synthetically (Clardy and Walsh, 2004;Nicolaou and Snyder, 2004;Peterson and Overman, 2004;Koehn and Carter, 2005). Many structural features common to natural products (e.g., chiral centers, aromatic rings, complex ring systems, degree of molecule saturation, and number and ratio of heteroatoms) have been shown to be highly relevant to drug discovery efforts (Lee and Schneider, 2001;Feher and Schmidt, 2003;Clardy and Walsh, 2004;Piggott and Karuso, 2004;Koehn and Carter, 2005).…”
Section: Importance Of Medicinal Plants In Drug Discoverymentioning
confidence: 99%
“…On the other hand, the stereoselective formation of chiral quaternary centers remains a challenging subject in asymmetric synthesis; thus, we deemed it of interest to examine the applicability of chiral bis‐sulfoxide/ N ‐oxide ( R , R )‐ 2 in the enantioselective allylation of hydrazones derived from α‐keto esters. If successful, this protocol will create a new quaternary center in the product, which can be derivatized to biologically active α‐allyl α‐amino acids (Scheme ) …”
Section: Introductionmentioning
confidence: 99%